Fabrication of Various Structures of Nanostraw Arrays and Their Applications in Gene Delivery. Issue 10 (7th March 2018) - He, Gen; Chen, Hui‐Jiuan; Liu, Di; Feng, Yuping; Yang, Chengduan; Hang, Tian; Wu, Jiangming; Cao, Yuhong; Xie, Xi
Abstract: Nanowires have a wide variety of biomedical applications, including drug delivery, cellular manipulation, cellular interfacing, and biosensing. Specifically, hollow nanowire arrays, or "nanostraws, " are recently developed to penetrate cell membranes and to provide temporal and dose controlled delivery of biomolecules into the cells. The fabrication of nanostraw arrays uses nanoporous membranes as starting templates. However, nanoporous membranes with custom‐designed diameters and densities are often expensive or commercially unavailable. As a result, nanostraws reported in literature consist of a limited number of structures with restricted applications. In this work, a simple approach of preparing nanostraws with differing structures, including various diameters, lengths, and densities, is developed. Furthermore, the application of nanostraws in gene transfection is assessed. To fabricate the nanostraw arrays, O2 plasma etching is applied to the template membrane with a desirable pore density to produce nanopores with matching sizes. Then, a series of nanostraws with controllable diameters, densities, and lengths is consistently fabricated. Finally, the nanostraws are integrated with a microfluidic device to penetrate the cell membrane or coupled with external techniques to achieve DNA transfection. This work demonstrates a simple yet versatile approach to fabricate a variety of hollow nanowires for broad biomedical device applications. Abstract : Hollow nanowire array, or "nanotraw", was recently developed to penetrate cell membrane and to provide temporal and dose control of the delivery of biomolecules into cells. In this work, a simple approach of preparing nanostraws with different structures including various diameters, lengths, and densities is developed, and their applications in gene transfection are explored.